Über Unterwanderung. - Koether, Jutta (Köln : Galerie Sophia Ungers, 1989)
Koether, Jutta ; Atkinson, Terry ; Koepcke, Arthur ; bonde, Peter ; Büttner, Werner ; Kippenberger, Martin ; Gudmundsson, Sigurdur ; Carstensen, Claus ; Ungers, Simon M. ; Staehle, Wolfgang ; Polke, Sigmar ; Herold, Georg ; Wallinger, Mark ; Bijl, Guillaume ; Copers, Leo ; Broodthaers, Marcel ; IFP
Über Unterwanderung, Galerie Sophia Ungers, Köln, 1989
boek